Implementation of the Divergence-Free and Pressure-Oscillation-Free Projection Method for Solving the Incompressible Navier-Stokes Equations on the Collocated Grids (Communications in Computational Physics, 2007)
In this paper, a divergence-free and pressure-oscillation-free projectionmethod for solving the incompressible Navier-Stokes equations on the non-staggeredgrid is presented. The exact discrete projection method is used to compute the velocityfield, which ensures the discrete divergence of the velocity field is zero. In order toeliminate the odd-even decoupling in the pressure field, a filtering procedure is proposed and applied to the pressure field. We have shown this filter recovers the gridscale ellipticity in the pressure field and the odd-even decoupling can be removedeffectively. The proposed numerical scheme is further verified through numerical experiments.